Thoughts on the nude body (Lebenswelt. Aesthetics and philosophy of experience., 2016)
The image of nude appears to have ‘moved’, both because of the shift in our gaze and its point of reference. That is, unless this ‘negative emphasis’ is seen only as the uncritical acceptance of that ‘polarizing question’ that declared the end of Classical art and the decisive advent of modernity or as the effect of an hermeneutic excess ‒ of a philosophical definition of the nude implicit in our figurative culture – is it now the moment to go beyond the observation of the canonic nude and to develop new approaches to nudity? Despite its obviousness, the nude, too, is difficult to define. Where does the garment begin and the gown end? The skin and the flesh? How are we to describe the forces, movements and gestures of the body and its involucres?I will argue that the nude should be neither a pictorial genre nor a philosophical concept, but a «thought of the body» (De Chirico). It is an aesthetic figure with the power of affection and perception, but also a conceptual figure. It is not a ‘critical operator’ ‒ a cognitive ‘walk-on’ or extra ‒ but an actor with the power of speech, capable of forming and transforming new relationships with observers.